2021
DOI: 10.5812/jjnpp.112353
|View full text |Cite
|
Sign up to set email alerts
|

Red Ginger Oil Affects COX-2 and NMDAR Expression During Inflammatory- or Neuropathy-Induced Chronic Pain in Mice

Abstract: Background: Chronic pain treatment until now is still challenging because of its complex pathopgysiology. Previously, red ginger oil (RGO) reduced pain behavior in a mouse model of chronic pain, but the mechanisms were unclear. Objectives: This study examined the effect of RGO on cyclooxygenase (COX)-2 and the N-methyl-D-aspartate receptor (NMDAR) using inflammatory- or neuropathy-induced chronic pain in mice. Methods: Red ginger was distilled with composition 1:2 using water. The acute toxicity of RGO was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…It is possible that ginger’s anti-inflammatory properties could improve a person’s health acutely. This validates earlier research’s findings that ginger supplementation may be able to prevent the COX-2 inflammatory pathway, which raises oxidative stress and unfavorable cytokine inflammation ( Fajrin et al, 2021 ). In addition to decreasing NF-κB activity, [6]-gingerol also inhibits the production of TNF-α, cyclooxygenase 2, and the by-products it generates, such as PGE2.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that ginger’s anti-inflammatory properties could improve a person’s health acutely. This validates earlier research’s findings that ginger supplementation may be able to prevent the COX-2 inflammatory pathway, which raises oxidative stress and unfavorable cytokine inflammation ( Fajrin et al, 2021 ). In addition to decreasing NF-κB activity, [6]-gingerol also inhibits the production of TNF-α, cyclooxygenase 2, and the by-products it generates, such as PGE2.…”
Section: Discussionsupporting
confidence: 91%
“…The inflammation process generally induces the release of inflammatory mediators such as prostaglandin (PGE2) via the activation of the cyclooxygenase-2 (COX-2) enzyme. Pain can be reduced if the COX-2 activity is reduced in the hypothalamus, and it has been proven through in vivo research that mice induced by red ginger oil at a dose of 600 mg/kg showed the best activity in reducing COX-2 expression in the hypothalamus [5].…”
Section: Introductionmentioning
confidence: 99%